FINANCIAL ANALYSIS OF TOURISM, RESTAURANT, HOTEL COMPANIES: PRE- PANDEMIC AND COVID-19PANDEMIC PERIOD - Angel Febiyanti; Rini Tri Hastuti (International Journal of Application on Economics and Business, 2024)
This research aims to evaluate the differences in the financial condition of companies in the hotel, restaurant and tourism sub-sectors listed on the Indonesia Stock Exchange during the pre-pandemic period (2018-2019) and in the midst of the Covid-19 pandemic (2020-2021). Using three financial indicators (liquidity, profitability, and solvency), the research involved 120 samples from 10 companies using purposive sampling. Through a quantitative approach and data analysis using Microsoft Excel and SPSS 26 with paired sample t-test, the research findings indicate variability in financial performance, measured through the Current Ratio (CR), Return on Assets (ROA), and Debt to Equity Ratio (DER), between the pre-pandemic and Covid-19 pandemic periods. The implication is to provide in-depth understanding and crucial insights for business practitioners and stakeholders in maintaining the corporatefinances through financial ratio analysis, especially in facing unpredictable economic dynamics.